Analisis BTS Initial Planning Jaringan Komunikasi Selular PT. Provider GSM di Sumatera - Eva Yovita Dwi Utami; Nabella Previana Yosinta; Budihardja Murtianta (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
Initial planning of cellular communication network is required before implementing new BTSs. This paper reports an analysis of BTS initial planning based on existing coverage area data using ASSET Tools simulation software. Coverage area on operational area of GSM service provider in Sumatera is simulated to obtain 95% coverage. The operational area of the provider includes Sumatera Utara, Sumatera Barat, Riau and Kepulauan Riau. Okumura-Hata propagation model is used in this simulation. In each province, four clutters have been investigated, which are dense urban, urban, sub urban and rural. The result shows that urban and sub urban clutter in Sumatera Utara fulfill the target of 95%, all clutters of Sumatera Barat and Riau reach the target of 95%, while only sub urban and rural clutter of Kepulauan Riau reach the target. Total amount of BTS which has been added to cover Sumatera area are 853 BTSs, which consist of 305 BTSs in Sumatera Utara area, 151 BTSs in Sumatera Barat area, 306 BTSs in Riau area, and 91 BTSs in Kepulauan Riau.